La crise économique et le marché immobilier - Daigneault, André (Assurances, 1983)
The author, Mr. André Daigneault, describes the real estate market at the present time. In particular, he distinguishes between an individual building, a rental location and a commercial building, which all differ from one another. For individual buildings and rental accommodation, more construction would be possible if the costs were not so high. The situation is now a little better, due to the reduction in interest rates. As for commercial buildings, the rents are high but too much space is available due to the amount of construction which has taken place in Montreal and the rest of Canada. The problem is no longer to build, but to fill.